Students’ failure to understand fraction multiplication as part of a quantity - Purnomo, Yoppy Wahyu; Pasri; Aziz, Tian Abdul; Shahrill, Masitah; Prananto, Irfan Wahyu (Journal on Mathematics Education, 2022)
In the body of knowledge in mathematics education research, fractions are one of the researchers’ concerns. The reason is because fractions are very difficult for students to understand. This study explores elementary school students’ knowledge and obstacles in dealing with the multiplication of fractions. This study employs descriptive quantitative and qualitative approaches. Data were collected using the fractional knowledge test administered to 56 fifth-grade students and cognitive semi-structured interviews with six students depending on their test scores. The results of this study show that students’ knowledge of fractions is restricted, with challenges interpreting context-based problems and the usage of “of” terms. Another finding shows that students’ procedural knowledge is more dominant than conceptual knowledge. To develop students’ knowledge of fractions, the portion of context-based learning must be an emphasis. The importance of developing research-based textbooks based on a suitable learning trajectory is highlighted.